Functional outcome of open reduction and internal fixation of clavicle fracture - Pillai, Manju G. (International Journal of Research in Medical Sciences, 2017)
Background: Clavicle fracture is one of common bony injury; which is more common in young active individual. It has been traditionally treated with non-operative method. This present study was undertaken to study the role of the surgical management in the fresh middle third clavicle fracture. Methods: 30 adult patients (21 male and 9 female) of average age of 32 years presented with fresh middle third clavicle fracture and treated surgically with open reduction and internal fixation with plate and screws and followed. Study conducted between November 2011 to November 2012. Results: In 27 patients fracture were united at end of 12 weeks, in 2 patients fracture were united at end of 24 weeks and 1 patient went for non-union. One patient had superficial infection. None had deep infection. One patient had plate loosening at 4week but fracture was united at the end of 24 weeks. 2 patients had persistent pain which is controlled with occasional analgesic but not effecting ordinary work. One patient had gross restriction of shoulder movement. Functional outcome assessed according to near shoulder scoring system. 24 patients had excellent result, 4 patients had satisfactory result, 1 patient had unsatisfactory result and 1patients had failure. Conclusions: The study showed rigid fixation with plate and screw for fresh middle third clavicle fracture especially displaced and comminuted give immediate pain relief and prevent the development of shoulder stiffness &non-union and give good functional outcome.